“Parar um minuto, olhar para trás e seguir adiante”: organização de mulheres do MST no assentamento 10 de Abril - Pageú, Ohana de Alencar (2017)
The present research seeks to analyze how sex / gender relations are inserted in the northeastern agrarian space, taking as study the struggle for land in Settlement 10 de Abril, located at Crato, it’s being the first settlement organized by the MST in the southern state of Ceará. This experience is embedded in the complex reality of northeast, where this research, up to the place of women in the construction of spatial relations in the countryside, seek to understand the involvement of political and socioeconomic access process to the land with relations of sex / gender. The approach adopted was a qualitative research, which dealt with the differences found in the spaces of struggle (camp and settlement), helping to identify changes in workers' understanding of historically determined, of men and women, at private sphere (domestic environment) and public (productive work and political environment), at the starting point, the role of women in Settlement 10 de Abril. Furthermore, to understand how MST acts in the deconstruction of these social relations, for the organization to the workers. It was a bibliographic analysis on the northeastern agrarian space, the relations of sex / gender and the organization of social movements , as well as a survey of theoretical production of MST. Using semi-structured interviews with women and who were involved in the organizational process of the Settlement 10 de Abril, in addition to visits and interviews to government institutions responsible for technical implementation of agrarian reform and establishment of the settlement. As deepening into historical sources, in the reality and reviews of the interviewed women, it is perceived how the female social subject has a double confrontation: the fight for social rights with the working class and struggling, inside this same class, by political space, combating gender / gender inequality. In this sense, the contradictions narrated by the women of Settlement 10 de Abril bring us the difficulties they face within the fight in obtain and remain in the construction of a collective productive space in the settlement; to perceive the advances of consciousness, from the experience lived in the fight for land; in resist to the advance of agribusiness and the lack of a real and effective project of National Agrarian Reform. This way, this paper seeks to reaffirm this theme as the axis of an important geographical analysis of agrarian space, providing greater knowledge of reality to the historic task of changing the lives of the working class.